SENSE OF HUMOR RELEVANSINYA TERHADAP TEACHING STYLE (TELAAH PSIKOLOGI PENDIDIKAN ISLAM) - Idi Warsah; Asri Karolina; Yesa Satriya Dwi Hardiyanti (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
Humor is very often done by hurting other people’s feeling especially amid students. Teachers’ less understanding of proper teaching styles tend to lead them to use humor as the style of teaching. This way is not justified in the Qur’an. On the other side, humor is an important element in enhancing students’ learning motivation on account of fun learning it creates. Thus, the purposes of this study are to find out how the sense of humor is viewed in the perspective of Islamic educational psychology, and to investigate the extent to which humorous sense is relevant to teaching styles. This study used a normative qualitative approach (library research) wherein the data were garnered from books, articles, and other sources relevant to the study foci, especially books of commentaries addressing the verses of humor in the Qur-an as well as books addressing teaching styles using humor. This study revealed that in a verse of the Qur’an, Allah SWT does not prohibit His slaves to do humor and to laugh as long as such deeds are still within the agreed boundary taught in the Qur’an. Subsequently, according to the books of teaching styles, using humor is needed to enhance students’ motivation so that the teachers skillful at humor are required in the perspective of Islam.